Reimagining Educational Success: Lessons on Support, Wellbeing, and Trust from Community-Grounded Research with Black Families and Gender-Diverse Youth (LEARNing Landscapes, 2024)
We present a dialogue between two community-based scholars in Tio’tia:ke/Montréal, who are examining the experiences of low-income Black families and youth, and gender-diverse, homeless youth. We argue that success must be understood differently in light of the systemic discrimination many youth navigate in schools and explore how research may mirror experiences of discrimination and lack of access that youth navigate in schools. The article highlights how relational research approaches may provide lessons for supporting youth and community leadership and posits that we must foster deep practices of trust-building, shared aims for research impact, and trust in youth.
Keywords: community-based research; Black families and youth; gender-diverse youth; youth wellbeing; low-income youth